Sociolinguistics as a pathway to global citizenship: critically observing 'self' and 'other'. Issue 4 (2nd October 2021) - Abe, Sayaka; Shapiro, Shawna
Abstract: In this article, we discuss how sociolinguistics can serve as an entryway into conversations about diversity, equity, and social justice, as part of education for global citizenship. Our approach, informed by Critical Language Awareness (CLA) theory, engages students with both unfamiliar and familiar linguistic forms, in order to promote critical reflection on 'self' and 'other', a crucial component of global citizenship development in higher education. We draw on our experience teaching cross- and intra-linguistic variation in linguistics courses, using a curricular sequence that involves three central concepts: Descriptivism, Indexicality, and Language Ideology. Through this sequence, students become more aware of their implicit biases and learn to argue against pervasive linguistic stereotypes and misconceptions. We reference examples of student work and comments from course evaluations showing how students internalise and apply course learning. This study adds to the growing body of research on how CLA is taught and learned within the higher education curriculum. Supplemental data for this article is available online at https://doi.org/10.1080/09658416.2021.1925289 .